Southernmost record of Yellow-headed Vulture, Cathartes burrovianus Cassin, 1845 (Cathartiformes, Cathartidae), in Buenos Aires Province, Argentina - Colombo, Martín (2018)
We report the southernmost record of Yellow-headed Vulture, Cathartes burrovianus, in Punta Piedras, north-eastern Buenos Aires province, Argentina. This record implies the presence of this species in a new habitat: the Pampas ecoregion. Considering this and other records in Argentina and Uruguay, the species distribution could be extending south from its known range.